Thinking about Thoughts in Practising Psychotherapy - Rossouw, Gabriel (The Indo-Pacific journal of phenomenology, 2015)
By juxtaposing a phenomenological-existential mode of understanding with the mainstream therapeutic modality of cognitive behavioural therapy, this paper considers how the mode in which a therapist chooses to understand a client's thoughts may manifest in practice, and the potential implications thereof for the authenticity and effectiveness of the therapeutic process. In conclusion, the author points to the similar challenges confronting both client and therapist when thoughts are heard, despite the clamour of the collective voice, as a call from the lived to the self to explore its own possibilities.